Learning Mathematics through virtual mode: A review of literature (Siddhajyoti Interdisciplinary Journal, 2022)
This paper identified the gap in existing literature in virtual learning environment in Mathematics. About seven books, twenty-nine journal articles, four conference papers and eight doctoral dissertations were collected from five different websites (Research gate, Elsevier, Wolfram Alpha, Directory of open access journals and Semantic scholar) and four electronic databases (Pro Quest Dissertations & Theses Global, Google Scholar, ERIC and Science Direct). The collected literature was reviewed thematically. The literature indicated that virtual learning is the useful learning process and an opportunity for higher education as well as school level to continue formal education from home, although it has many challenges. Although there are fewer number of studies on the virtual learning environment in Mathematics, some studies emphasise combined use of virtual manipulative and physical manipulative to increase the mathematical ability. Also, some literature indicates that online learning is more effective than traditional classroom learning but the rate of completion online mathematics course is lower than the classroom learning.